Identification of Mutation Regions on NF1 Responsible for High- and Low-Risk Development of Optic Pathway Glioma in Neurofibromatosis Type I - Xu, Min; Xiong, Hui; Han, Yanfang; Li, Chijun; Mai, Shaozhen; Huang, Zhongzhou; Ai, Xuechen; Guo, Zhixuan; Zeng, Fanqin; Guo, Qing (Frontiers in Genetics, 2018)
Neurofibromatosis type I is a rare neurocutaneous syndrome resulting from loss-of-function mutations of NF1. The present study sought to determine correlations between mutation regions on NF1 and the risk of developing optic pathway glioma (OPG) in patients with neurofibromatosis type I. A total of 215 patients with neurofibromatosis type I, from our clinic or previously reported literature, were included in the study after applying strict inclusion and exclusion criteria. Of these, 100 patients with OPG were classified into the OPG group and 115 patients without OPG (aged ≥ 10 years) were assigned to the Non-OPG group. Correlation between different mutation regions and risk of OPG was analyzed. The mutation clustering in the 5’ tertile of NF1 was not significantly different between OPG and Non-OPG groups (P = 0.131). Interestingly, patients with mutations in the cysteine/serine-rich domain of NF1 had a high risk of developing OPG (P < 0.05), whereas those in the HEAT-like repeat region had a low risk (P < 0.05). This study confirms a new correlation between NF1 genotype and OPG phenotype in patients with neurofibromatosis type I, and provides novel insights into molecular functions of neurofibromin.